The search for a subsurface ocean in Ganymede with Hubble Space Telescope observations of its auroral ovals. Issue 3 (12th March 2015) - Saur, Joachim; Duling, Stefan; Roth, Lorenz; Jia, Xianzhe; Strobel, Darrell F.; Feldman, Paul D.; Christensen, Ulrich R.; Retherford, Kurt D.; McGrath, Melissa A.; Musacchio, Fabrizio; Wennmacher, Alexandre; Neubauer, Fritz M.; et al.
Abstract We present a new approach to search for a subsurface ocean within Ganymede through observations and modeling of the dynamics of its auroral ovals. The locations of the auroral ovals oscillate due to Jupiter's time‐varying magnetospheric field seen in the rest frame of Ganymede. If an electrically conductive ocean is present, the external time‐varying magnetic field is reduced due to induction within the ocean and the oscillation amplitude of the ovals decreases. Hubble Space Telescope (HST) observations show that the locations of the ovals oscillate on average by 2.0° ±1.3°. Our model calculations predict a significantly stronger oscillation by 5.8° ± 1.3° without ocean compared to 2.2°±1.3° if an ocean is present. Because the ocean and the no‐ocean hypotheses cannot be separated by simple visual inspection of individual HST images, we apply a statistical analysis including a Monte Carlo test to also address the uncertainty caused by the patchiness of observed emissions. The observations require a minimum electrical conductivity of 0.09 S/m for an ocean assumed to be located between 150 km and 250 km depth or alternatively a maximum depth of the top of the ocean at 330 km. Our analysis implies that Ganymede's dynamo possesses an outstandingly low quadrupole‐to‐dipole moment ratio. The new technique applied here is suited to probe the interior of other planetary bodies by monitoring their auroral response to time‐varying magnetic fields.